HOAKS WAJAH MORAL KITA - M. Januar Ibnu Adham (Journal of Innovation Research and Knowledge, 2021)
This research is intended to untangle hoax in the lens microscopic of moral as representation of our face. The researchers employed qualitative descriptive. To collect data, the researchers utilised interview and documentation. Result and discussion in this research showed that all the participants who have involved in this research comprehended about hoax terminology. Only most of them who have checked the validity about the news. Critical thinking is a panacea to test a news which is acquired. Hoax is amoral attitude. As a common, all the participant believes national media did not create a hoax for certain reason. As a result, critical literacy to audiences must be implemented by sustainable in order that the they think critically and they have knowledge to distinguish a hoax or not.